Correction: Microemulsion based synthesis of Ni/MgO catalyst for dry reforming of methane. Issue 56 (14th September 2020) - Rashid, Muhammad Usman; Daud, W. M. A. Wan
Abstract : Correction for 'Microemulsion based synthesis of Ni/MgO catalyst for dry reforming of methane' by Muhammad Usman et al., RSC Adv., 2016, 6, 38277–38289, DOI: ; 10.1039/C6RA01652A .